PENDUGAAN INFILTRASI MENGGUNAKAN DATA NERACA AIR DI SUB DAERAH ALIRAN SUNGAI WATUJALI, GOMBONG (Estimation of infiltration based on water balance method at Watujali Sub Watershed, Gombong) - Irfan Budi Pramono; Rahardyan Nugroho Adi (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2017)
Infiltration rate in a watershed is very important for water management. There are many methods for estimating the rate of infiltration in a watershed. Among of them are direct measurements, hydrograph analysis and water balance calculation. The purpose of this study was to estimate infiltration in the sub watershed  under pine forest. The method was based on a relationship between water balance and regression of monthly rainfall and discharge. The results showed that the infiltration rate of pine forest in Watujali Sub Watershed  range from 125 mm/year up to 1,193 mm/year. The infiltration rate was highly depended on rainfall as the input. In  2010 with 5,826 mm rainfall, the infiltration rate reached 1,193 mm/year. Estimation of infiltration using water balance data was easy to implement because it only used data of streamflow, rainfall and evapotranspiration.